Sampling frequency affects estimates of annual nitrous oxide fluxes - Barton, L.; Wolf, B.; Rowlings, D.; Scheer, Clemens; Kiese, Ralf; Grace, Peter; Stefanova, K.; Butterbach-Bahl, Klaus (Springer, 2015)
Quantifying nitrous oxide (N 2 O) fluxes, a potent greenhouse gas, from soils is necessary to improve our knowledge of terrestrial N 2 O losses. Developing universal sampling frequencies for calculating annual N 2 O fluxes is difficult, as fluxes are renowned for their high temporal variability. We demonstrate daily sampling was largely required to achieve annual N 2 O fluxes within 10% of the ‘best’ estimate for 28 annual datasets collected from three continents—Australia, Europe and Asia. Decreasing the regularity of measurements either under- or overestimated annual N 2 O fluxes, with a maximum overestimation of 935%. Measurement frequency was lowered using a sampling strategy based on environmental factors known to affect temporal variability, but still required sampling more than once a week. Consequently, uncertainty in current global terrestrial N 2 O budgets associated with the upscaling of field-based datasets can be decreased significantly using adequate sampling frequencies.